Data on changes in the fatty acid composition during fruit development and ripening of three mango cultivars (Alphonso, Pairi and Kent) varying in lactone content - Deshpande, A. B.; Chidley, H. G.; Oak, P. S.; Pujari, K. H.; Giri, A. P.; Gupta, V. S. (Data in Brief, 2016)
Data in this article presents fatty acid composition of three mango cultivars; Alphonso, Pairi and Kent through fruit development and ripening. Change in the ω-6 and ω-3 fatty acids level during mango fruit development and ripening is depicted. Also, data on aroma volatile ‘lactones’ composition from pulp and skin tissues of these cultivars at their ripe stage, respectively is provided. Statistical data is also shown, which correlates modulation in lactone content with that of fatty acid composition and content during fruit development and ripening in all the three mango cultivars.

Data on metabolic profiling of spongy tissue disorder in Mangifera indica cv. Alphonso - Oak, P. S.; Deshpande, A. B.; Pujari, K. H.; Prabhudesai, S. S.; Giri, A. P.; Gupta, V. S. (Data in Brief, 2019)
Data in this article presents aroma volatiles and fatty acids composition of mesocarp specific malady namely spongy tissue disorder in Mangifera indica cv. Alphonso. Quantitative changes in various aroma volatile compound classes as well as saturated and unsaturated fatty acids in spongy tissue vis-à-vis healthy mesocarp have been analyzed throughout the development of the disorder. Statistical data analysis correlates the dynamic changes in the aroma volatiles composition to that of the modulation in the fatty acids profile.